University archives in India: issues, challenges and future trends, an analytical review. Issue 1 (January 2020) - Gautam, Meena
Abstract : Archives are the custodians of their organization's memory and are preserved as authentic sources of information about past events and activities. As with other types of organization, university archives are expected to conserve and manage their records professionally, based on sound records management practices and to archival standards. In India, although many universities are nearly or more than 100 years old, archives services have typically only been developed over the last two decades. They differ drastically in their records management policies, practices, collections, clientele and relationships with the administration, and in the types of issues and challenges they face in terms of their records management and archival practices. This case study examines three archives, those of the University of Delhi (the university established in 1922, and the archives in 2006), of Jamia Millia Islamia (1920 and 2006) and of Jawaharlal Nehru University, Delhi (1969 and 2004). The study examines how these archives reflect the history and evolution of their universities and the circumstances and timing of their establishment; it also considers the challenges they face in conservation, preservation and in providing access to the archives, especially in view of emerging digital archives and future ICT developments.